Is Mastery Motivation a Mediator of Relations between Maternal Teaching Behavior and Developmental Abilities in Children with Global Developmental Delay?. (4th May 2019) - Wang, Pei-Jung; Chen, Li-Chiou; Liao, Hua-Fang; Tu, Yu-Kang; Lu, Lu; Morgan, George A.
Abstract: Aims : Mastery motivation refers to a child's persistent attempts to solve problems and learn skills. The purpose of this longitudinal study was to examine whether children's mastery motivation-mediated relationships between early maternal teaching behavior and later developmental abilities in children with global developmental delay (GDD). Methods : Fifty-six dyads of mothers and their children with GDD (aged 24–42 months) were assessed two times, at study entry and 6-months later. Maternal teaching behaviors were assessed using the Nursing Child Assessment Teaching Scale. Children's developmental abilities and mastery motivation were measured using the Comprehensive Developmental Inventory for Infants and Toddlers and the revised Individualized Moderately Challenging Mastery Tasks, respectively. A Pearson correlation matrix was used to propose hypothetical models, and path analysis was used to examine the mediation effect. Results : Mastery motivation significantly mediated the relationship between maternal teaching behavior and children's cognitive, fine motor, and gross motor abilities 6 months later. Conclusions: Mothers' teaching predicted their children's development directly and also indirectly through the child's mastery motivation. The findings support the importance of the quality of mothers teaching behaviors and the mastery motivation of children with GDD on development.